Genetic Diversity of Potential Drug Resistance Markers in Plasmodium vivax Isolates from Panama, Mesoamerica - Vanessa Vásquez; Ana María Santamaría; Dianik Moreno; Fergie Ruíz; Chystrie A. Rigg; Luis F. Chaves; José E. Calzada (Pathogens)
This study evaluated the genetic diversity and potential drug resistance markers in Plasmodium vivax isolates from Panama, a country in Mesoamerica, aiming to eliminate local malaria transmission. We analyzed 70 P. vivax samples collected between 2004 and 2020 from endemic regions in Eastern and Western Panama, as well as imported cases. Four drug resistance genes (pvcrt-o, pvmdr1, pvdhfr, and pvdhps) were sequenced and analyzed. Our findings reveal low genetic diversity in P. vivax populations from Western Panama, indicating clonal expansion, while Eastern Panama exhibits higher diversity, influenced by higher transmission rates and imported cases. No mutations were detected in pvcrt-o, and the prevalence of pvmdr1 mutations (Y976F and F1076L) linked to chloroquine was observed at low frequencies, primarily in imported samples. In pvdhfr, antifolate-resistant mutations S117N and S58R were detected in 14.3% of samples, predominantly from Eastern Panama near the Colombian border. Phylogenetic and haplotype network analyses highlighted distinct genetic clustering, supporting the influence of imported cases on local parasite diversity. These results provide a baseline for the molecular surveillance of P. vivax in Panama and emphasize the need for the continued monitoring of genetic diversity and drug resistance to guide regional malaria elimination efforts, particularly in areas with high cross-border migration.